Recruitment and metabolomics between Canna indica and rhizosphere bacteria under Cr stress - Mao, Huan; Zhao, Wei; Yang, Xiuqin; Sheng, Luying; Zhu, Sixi (Frontiers in Microbiology, 2023)
It is of positive significance to explore the mechanism of antioxidant and metabolic response of Canna indica under Cr stress mediated by rhizosphere niche. However, the mechanisms of recruitment and interaction of rhizosphere microorganisms in plants still need to be fully understood. This study combined physiology, microbiology, and metabolomics, revealing the interaction between C. indica and rhizosphere microorganisms under Cr stress. The results showed that Cr stress increased the content of malondialdehyde (MDA) and oxygen free radicals (ROS) in plants. At the same time, the activities of antioxidant enzymes (SOD, POD, and APX) and the contents of glutathione (GSH) and soluble sugar were increased. In addition, Cr stress decreased the α diversity index of C. indica rhizosphere bacterial community and changed its community structure. The dominant bacteria Actinobacteriota, Proteobacteria, and Chloroflexi accounted for 75.16% of the total sequence. At the same time, with the extension of stress time, the colonization amount of rhizosphere dominant bacteria increased significantly, and the metabolites secreted by roots were associated with the formation characteristics of Proteobacteria, Actinobacteria, Bacteroidetes, and other specific bacteria. Five critical metabolic pathways were identified by metabolome analysis, involving 79 differentially expressed metabolites, which were divided into 15 categories, mainly including lipids, terpenoids, and flavonoids. In conclusion, this study revealed the recruitment and interaction response mechanism between C. indica and rhizosphere bacteria under Cr stress through multi-omics methods, providing the theoretical basis for the remediation of Cr-contaminated soil.